Collecting African American Art: the Museum of Fine Arts, Houston - Franklin, John Hope; Wardlaw, Alvia J (Museum of Fine Arts ; Yale University Press, 2009)
This important book showcases institutional and private efforts to collect, document, and preserve African American art in American's fourth largest city, Houston, Texas. Eminent historian John Hope Franklin's essay reveals his passionate commitment to collect African American art, while curator Alvia J. Wardlaw discusses works by Robert S. Duncanson, Henry Ossawa Tanner, Horace Pippen, and Bill Traylor as well as pieces by contemporary artists Kojo Griffin and Mequitta Ahuja. Quilts, pottery, and a desk made by an African American slave for his daughter contribute to the overview. The book also focuses on the collections of the "black intelligentsia," African Americans who taught at black colleges like Fisk University, where Aaron Douglas founded the art department. A number of the artists represented were collected privately before they were able to exhibit in mainstream museums.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Méthodologie de recherche décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé